Benign Enlargement of Subarachnoid Space in Infancy: “A Review with - Khosroshahi, Nahid; Nikkhah, Ali (Iranian Journal of Child Neurology, 2018)
Objective: Macrocephaly are among the most frequent reasons for referral to a pediatric neurologist. Benign enlargement of subarachnoid spaces (BESS) in infancy is a most common cause of macrocephaly and is characterized by excess cerebrospinal fluid (csf) in the subarachnohd spaces. In this review, we described epidemiology, etiology, clinical presentation, pathogenesis, neuroimaging, treatment and outcome of entity from current literature. Materials & Methods We searched the related papers in electronic databases such as Google Scholar, PubMed, and Scopus . Key words for searching were benign enlargement of subarachnoid spaces in infancy, external hydrocephaly and neuroimaging. Results The related data focusing on the etiology, epidemiology, clinical presentation, differential diagnosis, neuroimaging, treatment and outcome with emphasis on diagnostic work up were gathered and described. Conclusion BESS is most common cause of macrocephaly in infancy . It is characterized dy macrocephaly , excess csf in subarachnoid spaces and normal ventricles or mild ventricolomegaly. Self-limited disorder in infancy ,mostly in male and with familial tendency and normal or mildly delay motor or language delay. Mostly favorable prognosis without need treatment. Neuroimaging is essential for diagnosis and selection of useful tool and close observation of patient is necessary and sufficient for follow up. It is best way from economic points and reduce hazards of inappropriate neuroimaging.